Iron Profile and Clinical Patterns of Anemia Among Medical College Students (Medical Forum Monthly, 2020)
Objective: To determine the iron profile and clinical patterns of anemia in young medical college students,Study Design: Observational studyPlace and Duration of Study: This study was conducted at the Department of Pathology, Indus Medical College, T.M. Khan, Sindh, Pakistan from January 2018 to September 2019.Materials and Methods: A sample of 167 medical students was selected by non – probability convenient sampling. Volunteers were asked for blood sampling. 5 ml blood was drawn in disposable syringe. 2 ml was taken in EDTA tubes for the hematological indices and 3 ml was centrifuged to get sera for the estimation of serum iron, ferritin, TIBC and TSAT. Data was analyzed on SPSS 21.0 (USA) at 95% CI (P≤ 0.05).Results: Of 167 students; 99 (59.2%) were male and 68 (40.7%) were female. Age of male was 21.43±1.83 and female was 21.71±2.17 years (P=0.39). Normal and low serum Iron levels were noted in 60 (66.6%) vs. 31 (45.5%) and 39 (39.3%) vs. 37 (54.5%) of male and female respectively. Normocytic, microcytic and macrocytic anemia were noted in 63 (63.6%), 25 (25.2%) and 11 (11.1%) of male compared to 29 (42.64%), 31 (45.5%) and 8 (11.7%) of female respectively.Conclusion: The present study reports high frequency of low iron profile and anemia in young medical students.